A Portrait of Renewable vs. Non-Renewable Energy in Indonesia's Economic Dynamics - Muhammad Syahrul Hidayat (Journal of Economic Perspectives and Business Innovation, 2024)
AbstractThe dynamics of Indonesia’s economic development are closely linked to its energy structure, particularly the balance between renewable and non-renewable energy sources. This study provides an analytical overview of how both energy types contribute to economic growth, industrial productivity, and long-term sustainability. Using a mixed descriptive approach based on secondary economic and energy data, the research compares the economic impacts, environmental implications, and policy challenges associated with each energy sector. The findings indicate that non-renewable energy continues to dominate Indonesia’s economic activities due to infrastructure readiness and cost efficiency, while renewable energy shows strong potential for supporting sustainable growth and reducing environmental risks. However, barriers such as investment limitations, technological gaps, and regulatory constraints slow the transition toward cleaner energy. The study concludes that a balanced energy strategy integrating renewable expansion with responsible non-renewable management is essential for strengthening Indonesia’s economic resilience and sustainability. Keywords: renewable energy, non-renewable energy, Indonesia economy, energy transition, sustainable development